Molecular characterization and species composition of anopheline vectors of malaria along an altitudinal gradient on the highlands of Mambilla Plateau Northeast, Nigeria - Liatu Columbus, Garba; Florence A, Oyieke; Eunice Anyango, Owino; Georgina Samuel, Mwansat; Williams Chintem, D.G.W (African Journal of Biological Sciences, 2020)
Diversity of species arises majorly from speciation and this has serious epidemiological implications to disease transmission. The study aimed to determine the species of anopheline vectors of malaria present in five locations along with different altitudes on the highlands of Mambilla Plateau Nigeria. These are; Nguroje (1,885 m), Yelwa (1,674 m), Gembu (1,584 m), Kakara (1,496 m) and Mayo-selbe (484 m) above sea level. Samples were collected by Center for Disease Control (CDC) light trap, Pyrethrum Spray Catches (PSC) and others were reared from larvae. A total of 878 female anopheline mosquitoes comprising of five species namely; Anopheles gambiae sl 757(86.22%), Anopheles coustani 73(8.31%), Anopheles funestus 29(3.30%), Anopheles pharoensis 18(2.05%) and Anopheles rufipes 1(0.11%). Mayo-selbe had the highest species abundance of 572 but lowest species diversity index of 0.24 An. gambiae dominated over other anopheline species 0.76. Yelwa had the least abundance but very high diversity index of 0.81 dominance was 0.41. Out of the 757 An. gambiae tested by Polymerase Chain Reaction (PCR), 712(94.06%) were An. gambiae s.s., 192(25.37%) were M form and 520(68.69%) were S form. There was a very strong positive correlation between the M and S forms. As the M forms increase along the locations so also the S forms, r2 = 0.94204.
Keywords: Molecular, Anopheles gambiae, PCR, M and S form, Mambilla Plateau